2021
DOI: 10.3390/nano11082075
|View full text |Cite
|
Sign up to set email alerts
|

Coupling between Polymer Conformations and Dynamics Near Amorphous Silica Surfaces: A Direct Insight from Atomistic Simulations

Abstract: The dynamics of polymer chains in the polymer/solid interphase region have been a point of debate in recent years. Its understanding is the first step towards the description and the prediction of the properties of a wide family of commercially used polymeric-based nanostructured materials. Here, we present a detailed investigation of the conformational and dynamical features of unentangled and mildly entangled cis-1,4-polybutadiene melts in the vicinity of amorphous silica surface via atomistic simulations. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…In general, the behavior of polymer chains at interfaces is governed, by the strength of adsorption, the topological constraints imposed by other chains, such as entanglements, as well as the structure and the conformational heterogeneities of the adsorbed chains . Moreover, for systems with strong attractive polymer/substrate interactions, adsorbed chains might exhibit “glassy dynamics”, even at temperatures well above the glass transition, as observed both by simulations , and experiments . The slower relaxation modes inherited by attractive interfaces implicitly increase the necessary computational costs for studying such systems since more extended simulations are needed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, the behavior of polymer chains at interfaces is governed, by the strength of adsorption, the topological constraints imposed by other chains, such as entanglements, as well as the structure and the conformational heterogeneities of the adsorbed chains . Moreover, for systems with strong attractive polymer/substrate interactions, adsorbed chains might exhibit “glassy dynamics”, even at temperatures well above the glass transition, as observed both by simulations , and experiments . The slower relaxation modes inherited by attractive interfaces implicitly increase the necessary computational costs for studying such systems since more extended simulations are needed.…”
Section: Introductionmentioning
confidence: 99%
“…This is, in general, one of the most challenging tasks for atomistic simulations, since such interactions are typically the result of complex (many-body) physico-chemical phenomena, of quantum mechanical origin. In various studies, polymer/substrate interactions are described via the traditional Lorentz–Berthelot (LB) mixing rules, , or similar combination rules, such as the ones used by the COMPASS force-field (FF), due to their simplicity. Nevertheless, such semi-empirical functional forms are rather crude approximations, particularly for modeling the complex metal/polymer interfacial interactions .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cui et al [ 39 , 40 ] studied the effects of the incident angle of AO, energy flux density, the number of graphene layers, and the surface morphology on the ablation, and found that the surface morphology had a significant effect on the ablation rate. Bačová et al [ 41 ] presented an investigation of dynamics relations in thick films of cis-polybutadiene chains placed between rough amorphous silica slabs. The results suggested that the monomeric translational motion parallel to the surface was affected by the presence of the silica slab.…”
Section: Introductionmentioning
confidence: 99%